Pourghere soap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A factory to manufacture pourghere soap is currently being built on Santiago Island in Cape Verde. It is designed to produce 50 tonnes of soap per year using pourghere oil. This shrub, commonly used in reforestation programmes (6,000 seedlings this...